Magnetorheological suspension with capillary network. (July 2019) - Yang, Jianjian; Hu, Zhide; Yan, Hua; Niu, Fanghao
The capillary force has been employed to facilitate an effective pathway for the preparation and design of magnetorheological suspensions. The network formation from pendular particle structure-driven assembly can potentially be used to stabilize particle suspension. Furthermore, the magnetic liquid bridge proposed can give rise to a dramatic enhancement in magnetorheological effect (20%–100% increment in storage modulus), suggesting the possibility of tuning field dependent rheological properties of magnetorheological suspensions by addition of minute amounts of ferrofluid.